Industrial training report: Medical records department Tropicana Medical Centre (M) Sdn. Bhd. / Ezzatul Aisha Mokhtar - Mokhtar, Ezzatul Aisha (Bachelor of Information Science (HONS.) Records Management, 2015)
The Industrial Training subject (IMC 690) provides pre-professional work experience with specific assignments and responsibilities to be complete at the end of the internship programme. It involved 480 (four hundred eighty) hour equivalent work placement, paid or unpaid, located in an approved industrial site. Before the training begin, the student need to proposed place of their interested organization and must be approved by the faculty. The confirmation of the industrial training attachment is done once the coordinator received the offer letter from the relevant organization.